Carbohydrate and Fiber Intake on Fasting Blood Glucose Levels In Patients with Type 2 Diabetes Mellitus after Intervention of Brown Rice Diet - Chyntia Cahyawardani; Etik Sulistyowati; Endang Widajati (Indonesian Journal of Human Nutrition, 2023)
Type 2 diabetes mellitus (T2DM) is a metabolic disorder characterized by hyperglycemia that occurs due to a decrease in insulin secretion by pancreatic beta cells and insulin resistance. One of the pillars in the management of T2DM is medical nutrition therapy in the form of a balanced diet. A good intake of carbohydrates and fiber can help control fasting blood glucose levels of diabetic patients. This study aims to determine the relationship between carbohydrate and fiber intake on fasting blood glucose levels in patients with T2DM after the intervention of brown rice diet. The type used in this study was pre-experimental without control variables and the sample was not selected randomly. The design was one-shot case study by looking at the post-test results. The number of samples was 18 people aged 48–60 years. Data analysis used the Shapiro Wilk normality test and Spearman correlation test. The results showed that most of the respondents had normal carbohydrate intake (88.9%) and all respondents had good fiber intake (100%). Most of the respondents had uncontrolled fasting blood glucose levels (55.6%). There is no relationship between carbohydrate and fiber intake on fasting blood glucose levels after the intervention of a brown rice-based diet menu.